LEADERSHIP, LEARNING, AND CULTURE: HOW PRINCIPAL LEADERSHIP AND TEACHER EDUCATION DRIVE PERFORMANCE THROUGH ORGANIZATIONAL CULTURE - Maisusiyanti; Kristina Sedyastuti; Adi Suroso (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to examine the influence of principal leadership and teacher educational background on teacher performance, with organizational culture as a mediating variable at SMKN 1 Batu, a Center of Excellence Vocational High School. A quantitative approach with an explanatory design was employed. The sample consisted of 52 teachers selected through total sampling. Data were collected using structured questionnaires with a Likert scale and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The findings reveal that principal leadership, teacher educational background, and organizational culture each have a positive and significant direct effect on teacher performance, with organizational culture exhibiting the strongest influence. Furthermore, organizational culture serves as a significant mediator in the relationships between both principal leadership and teacher educational background on teacher performance. This study contributes a novel empirical insight by positioning organizational culture as a key mediating mechanism in the context of vocational education excellence, thereby offering practical implications for school leaders and policymakers. Specifically, strengthening leadership capacity, enhancing teacher qualifications, and fostering a collaborative school culture are essential strategies for achieving sustainable improvements in teacher performance.